Model Pembiayaan Pendidikan Berbasis Mutu dalam Pengembangan Pendidikan - Mahmud Siswandi; Edi Edi; Sutrisno Sutrisno (Ahlussunnah: Journal of Islamic Education, 2026)
This study examines the implementation of quality-based education financing as a strategic approach to supporting educational development and improving educational quality. Using a qualitative literature review approach, the study analyzes scholarly articles, academic books, policy documents, and educational regulations related to educational finance and quality management. Data were analyzed through content analysis involving data reduction, classification, interpretation, and conceptual synthesis. The findings indicate that quality-based education financing emphasizes the alignment of financial planning, resource allocation, implementation, and evaluation with educational quality objectives. Such an approach contributes to improved management effectiveness, enhanced learning services, greater financial transparency, and stronger achievement of educational quality standards. The analysis further reveals that leadership commitment, regulatory support, stakeholder participation, and digital financial management systems serve as key enabling factors, whereas budget limitations, inadequate oversight mechanisms, and limited financial management capacity remain significant challenges. This study proposes a conceptual framework for quality-based education financing that integrates accountability, transparency, innovation, and technology-based governance to support sustainable educational development. The findings contribute to the growing discourse on educational finance by highlighting the role of quality-oriented funding strategies in strengthening educational outcomes and institutional performance.